The rise of indigenous psychologies: In response to Jahoda's criticism. (December 2017) - Hwang, Kwang-Kuo
Based on his broad survey on a selection of the literature dealing with indigenous psychology, Jahoda raised a series of questions about various ways indigenous psychologists (IPists) around the world have answered important issues related to the development of indigenous psychology and found a striking lack of consensus in their proposals. He concluded that: "it is questionable whether any indigenous psychologies actually exist", "the fact help to explain the subsequent decline of the movement" (p. 169). Nevertheless, because his selection of literature was incomprehensive and biased, his comments on definitions of indigenous psychology, the goals of indigenous psychology, ways for building indigenous psychology, as well as the objective of a universal/global psychology are too hash to drew such a conclusion. Conceiving his viewpoints on those issues in the context of my approach for developing indigenous psychology, we may get an opposite conclusion that indigenous psychology will soon rehabilitate from its apparent disorder if and only if we can find appropriate ways to solve its difficult problems from the perspective of philosophy of science.